Dose Targeting Metrics in Conventional and Intensive Maintenance Dialysis. Issue 6 (4th September 2016) - Ananthakrishnan, Shubha; Depner, Thomas A.
Abstract: Hemodialysis has come a long way since its early days and is a life sustaining therapy for millions of people with end‐stage kidney disease throughout the world. Although thrice weekly hemodialysis remains the most common form of renal replacement therapy, other therapies such as more frequent, prolonged dialysis modalities have seen a rise recently. In this review, we compare and contrast methods for measuring the dialysis dose, with a focus on small molecule clearance ( Kt/V urea ) among various dialysis modalities. We also describe newer on‐line methods to measure dialysis and limitations to current adequacy measurement. Distinguishing dialysis adequacy from adequate treatment of the patient is also emphasized.